Influence of cytokine gene polymorphisms on graft rejection in Turkish patients with renal transplants from living related donors - Seyhun, Yalcin; Mytilineos, Joannis (Transplantation proceedings, 2012)
Introduction: Certain cytokine gene polymorphisms (CGPs) have been shown to be associated with renal transplant rejection or graft outcomes. We sought to evaluate the relationship between gene polymorphisms in patients with acute rejection episodes (rejection group, RG, n = 19) versus those with stable graft function (nonrejection group, NRG, n = 71) in comparison with healthy control subjects (HCG, n = 150). The follow-up time period was 18 months. In the present study, 22 single nucleotide polymorphisms distributed across 13 cytokine and cytokine receptor genes were genotyped by polymerase chain reaction sequence-specific primers (PCR-SSP) using the Heidelberg kit. Results: The interleukin-2 (IL-2) TT/GT haplotype was observed among 36.8% of patients in the RG and 6.7% of those in the HCG but not in any NRG patient (P < .0001; .0007). The IL-2 GG/TT haplotype was observed among 13 NRG and 9 HCG patients (P = .007). The IL-2 GG/GG haplotype was noted in 18.7% of HCG and 4.2% of NRG patients (P = .0033) and the IL-2 TT/TT haplotype in 5 and 8 patients of NRG and HCG, respectively, but not in any RG patient (P > .05). The transforming growth factor beta1 CG/CC haplotype was noted in 15 NRG (21.1%) and 4 HCG patients but not any RG (P < .0001). The IL-2 + 166 GT genotype was detected in 36.8% of RG, 8.5% of NRG, and 14.7% of HCG patients (P = .005, .0244). The IL-2 −330 GG genotype was demonstrated in 32 healthy controls and 3 nonrejection transplant patients (P = .0007). Significant differences were found between NRG and HCG for IL-6 565 AG, IL-1 beta −511 TT and +3962 CC/CT/TT genotypes. Discussion: We observed significant differences among the frequencies of IL-2 gene polymorphisms between the RG and the NRG, which were consistent with previous clinical but not in vitro studies.